Tagetes erecta mediated bio-synthesis of Mn3O4 nanoparticles: structural, electrochemical and biological investigations - Othman, Fezah; Hussain, Shabbir; Sagir, Muhammad; Muhammad Shahid, .; Refat, Moamen Salaheldeen; Mohammed Alsuhaibani, Amnah; Mustafa, Zeeshan; Tajammal, Affifa; Aslam, Ammara; Zakaria, Zainul Amiruddin (American Chemical Society, 2024)
Mn3O4 nanoparticles (NPs) find diverse applications in the fields of medicine, biomedicine, biosensors, water treatment and purification, electronics, electrochemistry, and photoelectronics. The production of Mn3O4 NPs was reported earlier through various physical, chemical, and green routes, but no studies have still been performed on their biosynthesis from Tagetes erecta. We synthesized manganese oxide NPs, i.e., (Mn3O4)L and (Mn3O4)P NPs, by utilizing leaves and petals, respectively, of T. erecta as reducing and stabilizing agents. The investigated green path is eco-friendly and does not involve any hazardous raw materials. The structural properties of NPs were determined by X-ray diffraction (XRD) analysis, spectroscopies (Fourier transform infrared (FTIR), Raman, and UV–visible), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The NPs were also evaluated for their electrochemical properties by cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD). XRD analysis was performed to verify their tetragonal geometry, and the crystallite size (19.24 nm) of (Mn3O4)P was smaller than that (20.84 nm) of (Mn3O4)L NPs. SEM images displayed a porous and spherical morphology with a diameter of 14–35 nm. FTIR spectra of (Mn3O4)L and (Mn3O4)P displayed Mn–O vibrations at 605.69 and 616.87 cm–1, respectively, and the hydrous nature of the material. Raman spectroscopy revealed the existence of tetrahedral and octahedral units along with A1g, T2g, and Eg active modes of Mn3O4 and 2TO mode. UV–visible analyses of (Mn3O4)L and (Mn3O4)P NPs showed absorption peaks at 272.3 and 268.8 nm, along with band gaps of 4.83 and 5.49 eV, respectively. TGA curves displayed good thermal stabilities up to 600 °C and a loss of moisture content. DSC curves exhibited exothermic/endothermic peaks with glass transition temperatures of 258.9 and 308.7 °C for (Mn3O4)P and (Mn3O4)L, respectively. The CV curves showed redox peaks and confirmed that the electrochemical reaction takes place in the Mn3O4 material. GCD scans revealed the capacitive behavior of NPs and their suitability as electrodes in energy storage devices. However, (Mn3O4)L will act as a good material for energy storage applications as compared to (Mn3O4)P NPs. The synthesized NPs were also tested for their antibacterial efficacy by biofilm inhibition and agar well diffusion methods. The NPs showed higher activities against Staphylococcus aureus (Gram-positive) than against Escherichia coli (Gram-negative), and (Mn3O4)P was more bioactive than (Mn3O4)L.